2014
DOI: 10.1002/cbic.201300623
|View full text |Cite
|
Sign up to set email alerts
|

An Ensemble of Rapidly Interconverting Orientations in Electrostatic Protein–Peptide Complexes Characterized by NMR Spectroscopy

Abstract: Protein complex formation involves an encounter state in which the proteins are associated in a nonspecific manner and often stabilized by interactions between charged surface patches. Such patches are thought to bind in many different orientations with similar affinity. To obtain experimental evidence for the dynamics in encounter complexes, a model was created using the electron transfer protein plastocyanin and short charged peptides. Three plastocyanins with distinct surface charge distributions were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 63 publications
(121 reference statements)
0
12
0
Order By: Relevance
“…It is possible that capsaicin could form an initial encounter complex with the TRPV1 molecule before binding more tightly in a manner mediated by the Y511 side chain conformational flip ( 62 ). Alternatively, it is possible that the absence of long-lived encounters between capsaicin and TRPV1 in the simulations imply that this ligand, in contrast to RTX, interacts only transiently with the channel.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that capsaicin could form an initial encounter complex with the TRPV1 molecule before binding more tightly in a manner mediated by the Y511 side chain conformational flip ( 62 ). Alternatively, it is possible that the absence of long-lived encounters between capsaicin and TRPV1 in the simulations imply that this ligand, in contrast to RTX, interacts only transiently with the channel.…”
Section: Discussionmentioning
confidence: 99%
“…(Martin et al, 2001) Because of the bias of the 40's loop for the 6-O-sulfated GalNAc in CS644, the non-reducing end (where the 6-O-sulfation is located) becomes associated with the 40s loop, thus the reducing end is more likely to be located at the N-loop. Because heterogeneous protein-ligand interactions are known to produce small chemical shift perturbations (Guan et al, 2014), the small chemical shift changes of the N-loop and N-terminal residues observed in the titration of CS644 may also be a manifestation of the heterogeneity in binding orientations of CS644. The change in chemical shift migration direction as the ratio of CS644-to-CCL5 goes beyond one maybe a sign of multiple ligand binding involving the N-loop.…”
Section: Discussionmentioning
confidence: 99%
“…As it does not, this must indicate that the hsc-70 LID domain is loosely tethered to the fluid-like nanodisc surface while bound. The situation is reminiscent of the delocalized interaction of DnaJ J-domain to DnaK (the Hsp70 of Escherichia coli) (19), cytochrome-cytochrome complexes (20), and nonspecific protein/DNA interactions (21), all of which are, like the hsc70/PS interaction, electrostatic in nature.…”
Section: Hsc-70mentioning
confidence: 99%